2020
DOI: 10.1002/lno.11548
|View full text |Cite
|
Sign up to set email alerts
|

Basal resource quality and energy sources in three habitats of a lowland river ecosystem

Abstract: Understanding energy flow through ecosystems and among sub-habitats is critical for understanding patterns of biodiversity and ecosystem function. It can also be of considerable applied interest in situations where managing for connectivity among habitats is important for restoring degraded ecosystems. Here, we describe patterns of basal resource quality and identify primary basal energy sources in three habitats-river channels, anabranches and wetlands-of a lowland river floodplain in the Murray River catchme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…These results have nutritional implications for riverine predators that as a direct result of river regulation and the reduction of large floodplain inundation events, have reduced access to floodplain prey. Previous work has shown that floodplain habitats can provide higher quality basal food resources for primary consumers than riverine habitats (McInerney et al, 2020), and here we identify one mechanism by which that may be extended to subsequent trophic levels (see Figure S5). Riverine crayfish contained the lowest proportion of LIN among all crayfish in the study.…”
Section: Wild Crayfish Fa Profiles and Implications For Food Websmentioning
confidence: 63%
See 3 more Smart Citations
“…These results have nutritional implications for riverine predators that as a direct result of river regulation and the reduction of large floodplain inundation events, have reduced access to floodplain prey. Previous work has shown that floodplain habitats can provide higher quality basal food resources for primary consumers than riverine habitats (McInerney et al, 2020), and here we identify one mechanism by which that may be extended to subsequent trophic levels (see Figure S5). Riverine crayfish contained the lowest proportion of LIN among all crayfish in the study.…”
Section: Wild Crayfish Fa Profiles and Implications For Food Websmentioning
confidence: 63%
“…Eight river and eight wetland sites were selected from the lower Ovens River floodplain, northeastern Victoria, Australia. Each river site was defined as a 200 m reach and wetlands known to permanently retain water were selected (for detailed descriptions of river and wetland habitats, see McInerney et al., 2020). Crayfish were sampled using collapsible shrimp traps baited with cow liver contained within plastic capsules to prevent consumption by crayfish.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Biofilms are mostly composed of algae and readily develop on the surface of leaves, woody debris and rocks. In particular, biofilms growing on rocks, also called epilithon, have been found to better support stream food webs than do terrestrial leaves due to their high PUFA content (Guo et al., 2016a; Lau et al., 2009; McInerney et al., 2020). However, in most previous studies, the method to sample these biofilms has not been uniform; a few studies collected biofilms on the upper side of the rock (light‐exposed biofilms; in short ‘light biofilms’), whereas most studies do not clarify whether the biofilms were only from the upper side or a combination of the upper side and underside of rocks.…”
Section: Introductionmentioning
confidence: 99%